2023
DOI: 10.1002/anie.202217020
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐fast One‐Handed Helix Induction and Its Static Helicity Memory in a Poly(biphenylylacetylene) with a Catalytic Amount of Chiral Ammonium Salts

Abstract: We report an ultra‐fast helix induction and subsequent static helicity memory in poly(biphenylylacetylene) (PBPA‐A) assisted by a catalytic amount of nonracemic ammonium salts comprised of non‐coordinating tetrakis[3,5‐bis(trifluoromethyl)phenyl]borate (BArF−) as a counter anion. The remarkable acceleration of the helix‐induction rate in PBPA‐A accompanied by the significant amplification of the asymmetry relies on the two methoxymethoxy groups of the biphenyl pendants, which can gain access to enfold the chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…In THF, the copolymers were also stable at 40 °C, although relatively weak Cotton effects appeared in poly­( 1c 0.995 - co -( R )- 3d 0.005 ) and poly­( 2 AO 0.95 - co -( R )- 3d 0.05 ) (Figure S28). Such a solvent-induced CD intensity change was frequently observed in PBPAs depending on the chiral and/or achiral pendant groups of PBPAs introduced at the 2,2′,4′-positions of the biphenyl units . In contrast, the previously reported helicity-memorized homopolymers ( h -poly- 1b , , h -poly- 1c , , h -poly- 1d , h -poly- 1e , and h -poly- 2 AO 30 ) prepared by the “noncovalent helicity induction and subsequent static memory of the helicity” approach gradually lost their helical sense preference under the same conditions due to the dynamic nature of the helicity memory (Figures g and S29).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In THF, the copolymers were also stable at 40 °C, although relatively weak Cotton effects appeared in poly­( 1c 0.995 - co -( R )- 3d 0.005 ) and poly­( 2 AO 0.95 - co -( R )- 3d 0.05 ) (Figure S28). Such a solvent-induced CD intensity change was frequently observed in PBPAs depending on the chiral and/or achiral pendant groups of PBPAs introduced at the 2,2′,4′-positions of the biphenyl units . In contrast, the previously reported helicity-memorized homopolymers ( h -poly- 1b , , h -poly- 1c , , h -poly- 1d , h -poly- 1e , and h -poly- 2 AO 30 ) prepared by the “noncovalent helicity induction and subsequent static memory of the helicity” approach gradually lost their helical sense preference under the same conditions due to the dynamic nature of the helicity memory (Figures g and S29).…”
Section: Resultsmentioning
confidence: 93%
“…21 was as intense as that of the completely one-handed helical poly-( S )- 1a (Δε 2nd = 21.1 (see Figure b)) in toluene at 25 °C . This result indicated that a one-handed helical conformation was almost completely induced in the poly-( R )- 3a backbone through the hierarchical chirality transfer from the point chirality of the 1-EE substituents to the axially chiral biphenyl units and further to the main-chain helicity. , The absolute helical senses of the one-handed helical PBPAs prepared in this study were unambiguously determined by high-resolution AFM (see below). As anticipated, poly-(+)- 3a -Ph, a homopolymer of an optically pure phenylacetylene bearing the same chiral 1-EE substituent ((+)- 3a -Ph), showed a negligibly weak CD in toluene at 25 °C (Figure S14), indicating the primary role of the axially chiral biphenyl units of poly-( R )- 3a for a one-handed helix induction …”
Section: Resultsmentioning
confidence: 99%
“…Helical poly­(phenylacetylene)­s (PPAs) are a class of intriguing polyene chiral polymers, which have been applied for various areas, including catalysis, chiral separations, and nanoparticle supports . PPAs adopt dynamic helical conformation through helix-inversion and/or cis - cisoid -to- cis - transoid conformational change due to the low helix-inversion barrier, and their chirality can be turned via various stimuli, including solvation, metal ion coordination, or solution temperature. , A series of reports demonstrated a prominent finding that dynamically racemic PPAs can be induced to adopt an excess one-handed helical conformation through ionic complexation with chiral amines or alcohols in organic solvents, whose chirality can be memorized even after complete removal of the chiral dopants. , Another more intriguing mechanism is the “chiral filter” effect due to the excess one-handed helical copolymers formed with the first L -amino acids, which could exclude one of the enantiomers in the racemic amino acid solution. These findings are remarkable and provide convenient routes to fabricate helical polymers with tailorable chirality simply through ionic complexation or dipolar–dipolar interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[14,[36][37] This phenomenon was denoted as "memory effect". [38] They found that this process can be extrapolated to other polyacetylene derivatives, such as poly(biphenylacetylene)s (PBPA) [39][40] and poly(diphenylacetylene)s (PDPAs). [41][42] These systems were recently denoted as first-(PPAs), second-(PBPAs) and third-(PDPAs) generation of static helicity memory respectively.…”
Section: Introductionmentioning
confidence: 99%